Connecting to Economic Opportunity? The Role of Public Transport in Promoting Women's Employment in Lima - Daniel Martinez; Oscar A. Mitnik; Edgar Salgado; Lynn Scholl; Patricia Ya\~nez-Pagans (Institute of Labor Economics (IZA), 2018)
Limited access to safe transportation is one of the greatest challenges to labor force participation faced by women in developing countries. This paper quantifies the causal impacts of improved urban transport systems in womens employment outcomes, looking at Bus Rapid Transit (BRT) and elevated light rail investments in the metropolitan region of Lima, Perú. We find large gains in employment and earnings per hour among women, and not for men, due to these investments. Most of the gains arise on the extensive margin, with more women being employed, but employment does not appear to be of higher quality than that for comparison groups. We find also evidence of an increase in the use of public transport. Results are robust to alternative specifications and we do not find evidence that they are driven by neighborhood composition changes. Overall, these findings suggest that infrastructure investments that make it more convenient and safer for women to use public transport can generate important labor market impacts for women who reside in the area of influence of the improved infrastructure.
Keywords: J01; J16; O12; R40; 330; urban transport; gender; employment; impact evaluation